Avaliação dos comportamentos auditivos de figura-fundo e de resolução temporal e da percepção de limitações de atividades comunicativas em crianças e adolescentes portadores de deficiência auditiva unilateral - Vieira, Márcia Ribeiro [UNIFESP] (2010)
Purpose: To test the hearing behavior of figure-to-ground and temporal resolution and the self-perception of limitations on activities of children and adolescents with unilateral hearing loss. Methods: Participated 38 individuals, between the age of 8 and 19 (average 12.32), divided into: experimental group (with unilateral hearing loss) and control group (normal-hearing individuals), each one formed of 19 individuals, matched according to their gender, age and educational level. They have all been submitted to anamneses, to a complete audiology test and to the procedures of study: a self-report questionnaire of limitations on communicative activities with questions about noisy and silent situations, and sound localization. The participants have been submitted to the Gap-In-Noise and the Pediatric Speech Intelligibility tests at 0, -10 and -15 reference. The statistical analysis has been done through non-parametric tests at the significance level of 0.05. Results: In the experimental group the unilateral hearing loss has been classified as profound in most participants, having started at the pre-schooling stage, with unknown or undefined etiologies (e.g. meningitis, traumas, mumps and measles). Most individuals have presented complaints of learning difficulties, and have shown limitations on communicative activities, of moderate degree predominantly, and especially in noisy situations. The degree and the ear with unilateral hearing loss have not interfered in the severity of the limitation. The worst results, both at the thresholds of gap detection and the Pediatric Speech Intelligibility test on the good ear, have been found in the experimental group. There was no correlation between the thresholds of gap detection on the good ear and the side of the bad one. Conclusions: Individuals with unilateral hearing loss present limitations on communicative activities, especially in noisy environments which are related to worse hearing abilities of temporal resolution and figure-to-ground.